Modeling the Impact of Stream Discharge Events on Riparian Solute Dynamics. Issue 1 (17th April 2018) - Mahmood, Muhammad Nasir; Schmidt, Christian; Fleckenstein, Jan H.; Trauth, Nico
Abstract: The biogeochemical composition of stream water and the surrounding riparian water is mainly defined by the exchange of water and solutes between the stream and the riparian zone. Short‐term fluctuations in near stream hydraulic head gradients (e.g., during stream flow events) can significantly influence the extent and rate of exchange processes. In this study, we simulate exchanges between streams and their riparian zone driven by stream stage fluctuations during single stream discharge events of varying peak height and duration. Simulated results show that strong stream flow events can trigger solute mobilization in riparian soils and subsequent export to the stream. The timing and amount of solute export is linked to the shape of the discharge event. Higher peaks and increased durations significantly enhance solute export, however, peak height is found to be the dominant control for overall mass export. Mobilized solutes are transported to the stream in two stages (1) by return flow of stream water that was stored in the riparian zone during the event and (2) by vertical movement to the groundwater under gravity drainage from the unsaturated parts of the riparian zone, which lasts for significantly longer time (> 400 days) resulting in long tailing of bank outflows and solute mass outfluxes. We conclude that strong stream discharge events can mobilize and transport solutes from near stream riparian soils into the stream. The impact of short‐term stream discharge variations on solute exchange may last for long times after the flow event. Abstract : Article impact statement : Short‐term stream stage fluctuations trigger long‐term solute mobilization within riparian zone and consequent transport to the stream.